Sborník o stavu příprav kandidátských zemí na připojení k Evropské unii (Czech Journal of International Relations, 2001)
Jiří Chlumský /ed./: Monitoring Preparations of Transition Countries for EU-Accession. 1st ed. Prague: Research Center of Integration of the Czech Republic into European Economy, 2000, 336 stran, ISBN 80-245-0102-3.